Intersetorialidade no Serviço de Proteção e Atendimento Integral à Família (PAIF) da política de assistência social de Fortaleza: uma avaliação em processo - Jacob, Cícero Renato Ribeiro (2014)
The research circumscribed in this argumentative work presents as its main object of investigation the evaluation of the intersectoral construction process in the Paif Social Assistance Reference Center (CRAS) of Mondubim, a neighborhood in Fortaleza . The research presents theoretical and methodological designs configured in epistemological postulations that mark the proposition of "open and critical rationalism" as proposed by Alba Carvalho, as a way of conceiving and doing science. In this sense, the methodological route of the research was done through bibliographical research, desk research and empirical research. Considering the theoretical and empirical demarcation, confined to the subject of the investigation, the construction of the analytical contributions of the research was structured based on the survey and the reading of scientific papers on the themes: State, poverty, social protection, public policy social assistance and intersectoral. The empirical field of the research is limited to the scope of institutional spaces which operationalize social assistance policy in Fortaleza, during the years 2012 and 2013, namely: Secretaria Municipal de Assistência Social; Distrito de Assistência Social da Secretaria Executiva Regional V; and, finally, Cras Mondubim. The research presents a qualitative approach, linking to the adoption of contributions of the quantitative approach. In this sense, interviews questionnaires were applied to 54 professionals of high and medium levels from Paif SER V and conducted in depth with 19 professionals and users (as) the Paif of Cras Mondubim. In the methodological research route, it was also carried out the survey and the analysis of documents and, finally, an intense process of Paif’s development observation was done in Cras Mondubim. With regard to the results marked by the research, we can point out: the interlocutors results – through differences on the analytical perspective and the specifications outlined by their speeches - postulate that the intersectoral category has a prominent place in the configuration of identity and the modus operandi of social welfare policy, indicating that the establishment of this category in the operationalization of programs, projects and services of social work marks an important route to its statement as a public policy of non-contributory social protection.